April Wheeler’s Tragic Unraveling: Exploring “Revolutionary Road” through Maslow and Inner Conflict - Petrina, Petrina; Oktavia, Yunisa (eScience Humanity Journal, 2025)
This analysis delves into two key issues centered around the hierarchy of needs in the female lead, April Wheeler. Primarily, it explores the unfulfilled nature of her needs and delves into the inner conflict that led to an imprudent choice, ultimately resulting in her tragic demise. The research aims to comprehensively examine the nuanced progression of psychological symptoms in April Wheeler, shedding light on the influential forces shaping her path. By applying established psychological theories, this study reveals the profound impact of mental health dynamics, providing valuable insights into the intricate interplay between psychological theories and literary character development. The object of the analysis is April Wheeler and her psychological trajectory throughout the narrative. Using qualitative methodology, this research involves a meticulous examination of April's psychological needs and conflicts, utilizing Maslow's Hierarchy of Needs and Lewin’s approach-avoidance dynamics. Data is collected through narrative analysis, transcription, and documentation, and subsequently segmented and analyzed. The research unfolds the multi-faceted layers of April's psyche, from the fulfillment of basic needs to the denial of self-actualization, offering a comprehensive understanding of her tragic journey. This research underscores the enduring relevance of literature in shaping our comprehension of the human psyche and encourages a profound exploration of mental health implications in our collective consciousness.